Chemical reactions of single optically trapped bioaerosols in a controlled environment. Issue 8 (3rd August 2019) - Gong, Zhiyong; Pan, Yong-Le; Videen, Gorden; Wang, Chuji
Abstract : Copyright © 2019 American Association for Aerosol Research